Anti-aging activity of Radix polygoni multiflori preparata in aging mice model induced by D-galactose by bioassay method - Jiang Yan Huo; Hong Chao Shen; Shu Mei Wang; Zhan Ke Chen; Sheng Wang Liang (Bangladesh Pharmacological Society, 2016)
Anti-aging effect of Radix polygoni multiflori preparata in aging mice model was examined by bioassay method and explore new model of quality control of Traditional Chinese Medicine. Model of aging mice induced by D-galactose were used. The activity of senescence associated molecular markers such as superoxide dismutase, malondialdehyde and glutathione peroxidase in serum or homogenate were determined to evaluate the anti-aging activity. The results showed that the polysaccharide content in the 0.4, 0.8 g/mL decoction were 80.1, 160.2 mg/mL respectively. The HPLC results showed that stibene glucoside content in the 0.4 and 0.8 g/mL decoction were 404 and 808 mg/mL respectively. Experimental results showed that 10 week-old mice were the most sensitive to SOD activity in homogenate. In conclusion, Radix polygoni multiflori preparata has anti-aging effect probably by removing ROS.